(untitled) (Kairaranga, 2015)
Te Kotahitanga is a Kaupapa Maori research and development programme that aims at improving Maori student achievement. Through interviews with students, teachers and whanau, the characteristics of teachers who made a difference were identified. These characteristics were drawn together to form the Effective Teaching Profile (ETP). This literature review provides a brief background on the Te Kotahitanga programme with an emphasis on the ETP, and its impact on Maori students’ achievement in secondary schools. The educational disparities that exist and perpetuate for indigenous (Maori) learners in Aotearoa/New Zealand are discussed as a rationale for implementing Te Kotahitanga in schools. This literature review explores the principles of the ETP and how these impact on Maori achievement. The ETP is also considered from a Resource Teacher: Learning and Behaviour (RTLB) viewpoint.